2014
DOI: 10.1007/s12020-014-0420-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between thyroid autoantibody status and abnormal pregnancy outcomes in euthyroid women

Abstract: We investigated whether thyroid autoantibody status influences pregnancy outcomes in euthyroid women, by comparing abnormal pregnancy outcome rates between those who tested positive for thyroid autoantibodies (Ab+) and those who tested autoantibody-negative (Ab-). Euthyroid pregnant women (n=7,641) underwent tests for serum thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). The subjects were divided into 4 groups according to thyroid antibody status: TPOAb-/TgAb- (92.9%); TPOAb+/TgAb- (3.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…The synthesis meta-analysis showed no significant association between TgAb and GDM, with a pooled RR of 1.34 (95% CI 0.93-1.95). The meta-analysis of the three cohort studies (16,18,19) demonstrated results similar to the association between TPOAb and GDM risk (pooled RR 1.23, 95% CI 0.78-1.95; Table 1). For all of these meta-analyses, no statistically significant heterogeneity was found, and fixed-effect models were used.…”
Section: Tgab and Gdmsupporting
confidence: 53%
See 4 more Smart Citations
“…The synthesis meta-analysis showed no significant association between TgAb and GDM, with a pooled RR of 1.34 (95% CI 0.93-1.95). The meta-analysis of the three cohort studies (16,18,19) demonstrated results similar to the association between TPOAb and GDM risk (pooled RR 1.23, 95% CI 0.78-1.95; Table 1). For all of these meta-analyses, no statistically significant heterogeneity was found, and fixed-effect models were used.…”
Section: Tgab and Gdmsupporting
confidence: 53%
“…In studies that included euthyroid women (9,10,15,19,20,24,25,28), the pooled RR of thyroid antibodies or TPOAb positive status on GDM incidence did not reach statistical significance (for thyroid antibodies, pooled RR 1.08, 95% CI 0.97-1.22; for TPOAb, pooled RR 1.06, 95% CI 0.94-1.20; Table 1; Fig. 3).…”
Section: Subgroup Analysismentioning
confidence: 95%
See 3 more Smart Citations